2024
DOI: 10.1177/17407745231217279
|View full text |Cite
|
Sign up to set email alerts
|

Patient-reported measures of tinnitus for individuals with neurofibromatosis type 2–related schwannomatosis: Recommendations for clinical trials

Heather L Thompson,
Jane Grabowski,
Barbara Franklin
et al.

Abstract: Background Neurofibromatosis type 2–related schwannomatosis is a genetic disease characterized by the development of bilateral vestibular schwannomas, ependymomas, meningiomas, and cataracts. Mild to profound hearing loss and tinnitus are common symptoms reported by individuals with neurofibromatosis type 2. While tinnitus is known to have a significant and negative impact on the quality of life of individuals from the general population, the impact on individuals with neurofibromatosis type 2 is unknown. Cons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 39 publications
0
1
0
Order By: Relevance
“…Tinnitus is a common presenting symptom in both types of VS patients. Up to 75% of patients with the sporadic form and 80% of patients with NF2-associated VS have tinnitus [ 15 , 55 , 56 ]. In a retrospective study, Naros et al found that most patients (61.8%) in their cohort of patients with sporadic and unilateral VSs presented with tinnitus prior to surgical management [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…Tinnitus is a common presenting symptom in both types of VS patients. Up to 75% of patients with the sporadic form and 80% of patients with NF2-associated VS have tinnitus [ 15 , 55 , 56 ]. In a retrospective study, Naros et al found that most patients (61.8%) in their cohort of patients with sporadic and unilateral VSs presented with tinnitus prior to surgical management [ 22 ].…”
Section: Discussionmentioning
confidence: 99%